BASIC LEGAL APPROACHES TO THE RECOGNITION AND ENFORCEMENT OF FOREIGN INTERIM JUDICIAL ACTS - BELYANINA MARIA (Legal Bulletin, 2025)
The relevance of the problem under consideration is due to the development of economic relations and insufficient regulation of issues related to international cooperation in the field of recognition and enforcement of intermediate judicial acts.